2000
DOI: 10.1007/s11894-000-0051-7
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the donor pool for liver transplantation

Abstract: Because of the growing shortage of donor organs, physicians and organ procurement agencies are expanding the donor pool through three mechanisms. The first mechanism is to increase the number of patients (and their families) who give consent for organ donation and thus extend the number of cadaveric livers. The second mechanism is that marginal livers, previously considered unacceptable for transplantation, are now being successfully transplanted. The third way to expand the donor pool is through advances in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Shortages of donor livers for orthotopic liver transplantation have become a major limiting factor in efforts to reduce mortality of patients with end-stage liver disease. 27 Therefore, alternative strategies to replace severely damaged livers must be developed. Studies in mice with mas- sive toxin-induced liver injury have demonstrated that liver cell transplantation can effectively regenerate the liver (reviewed in Forbes et al 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shortages of donor livers for orthotopic liver transplantation have become a major limiting factor in efforts to reduce mortality of patients with end-stage liver disease. 27 Therefore, alternative strategies to replace severely damaged livers must be developed. Studies in mice with mas- sive toxin-induced liver injury have demonstrated that liver cell transplantation can effectively regenerate the liver (reviewed in Forbes et al 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research exists on the public health challenges confronting organ donation and retrieval. Particular research emphasis has been placed on examining methods to increase the number of available organs for transplant, to narrow ethnic and other socioeconomic disparities that exist in the organ transplantation process, and to better delineate ethically and publicly acceptable approaches to organ procurement 4–19 . However, scant research exists on the role of EM and emergency health care providers in the organ procurement process 20–25 .…”
mentioning
confidence: 99%
“…Furthermore, marginal livers that are more vulnerable to I/R and other injuries are widely used nowadays to expand the donor pool. 36 It may also be advisable not to allocate marginal livers to liver patients already known to have LSEC antibodies.…”
Section: Discussionmentioning
confidence: 99%